Adjunctive β2‐agonist treatment reduces glycogen independently of receptor‐mediated acid α‐glucosidase uptake in the limb muscles of mice with Pompe disease. Issue 5 (21st January 2014) - Farah, Benjamin L.; Madden, Lauran; Li, Songtao; Nance, Sierra; Bird, Andrew; Bursac, Nenad; Yen, Paul M.; Young, Sarah P.; Koeberl, Dwight D.
ABSTRACT: Enzyme or gene replacement therapy with acid α‐glucosidase (GAA) has achieved only partial efficacy in Pompe disease. We evaluated the effect of adjunctive clenbuterol treatment on cation‐independent mannose‐6‐phosphate receptor (CI‐MPR)‐mediated uptake and intracellular trafficking of GAA during muscle‐specific GAA expression with an adeno‐associated virus (AAV) vector in GAA‐knockout (KO) mice. Clenbuterol, which increases expression of CI‐MPR in muscle, was administered with the AAV vector. This combination therapy increased latency during rotarod and wirehang testing at 12 wk, in comparison with vector alone. The mean urinary glucose tetrasaccharide (Glc4), a urinary biomarker, was lower in GAA‐KO mice following combination therapy, compared with vector alone. Similarly, glycogen content was lower in cardiac and skeletal muscle following 12 wk of combination therapy in heart, quadriceps, diaphragm, and soleus, compared with vector alone. These data suggested that clenbuterol treatment enhanced trafficking of GAA to lysosomes, given that GAA was expressed within myofibers. The integral role of CI‐MPR was demonstrated by the lack of effectiveness from clenbuterol in GAA‐KO mice that lacked CI‐MPR in muscle, where it failed to reverse the high glycogen content of the heart and diaphragm or impaired wirehang performance. However, the glycogen content of skeletal muscle was reduced by the addition of clenbuterol in the absence of CI‐MPR, as was lysosomal vacuolation, which correlated with increased AKT signaling. In summary, β2 ‐agonist treatment enhanced CI‐MPR‐mediated uptake and trafficking of GAA in mice with Pompe disease, and a similarly enhanced benefit might be expected in other lysosomal storage disorders.—Farah, B. L., Madden, L., Li, S., Nance, S., Bird, A., Bursac, N., Yen, P. M., Young, S. P., Koeberl, D. D. Adjunctive β2‐agonist treatment reduces glycogen independently of receptor‐mediated acid α‐glucosidase uptake in the limb muscles of mice with Pompe disease. FASEB J . 28, 2272–2280 (2014). www.fasebj.org